6 - The management of diabetes among the rural poor in South Africa - Olajide Oloyede, (African Sociological Review, 2015)
The objective of this study was to examine the management of diabetes mellitus Type 2 among the rural poor in South Africa. The focus group method was used. Data was elicited from 20 group sessions over a 20-week period on health beliefs and attitudes and rural-dwelling diabetes sufferers’ strategies for managing the condition. The study shows poor knowledge of diabetes and poor self-management as delineated in the medical literature. The focus of the rural dwellers’ self-management of diabetes was hypoglycaemic control through regular consumption of very-high-calorie food, the type of which have been found to lead to a diet that has very high carbohydrate, high in saturated fatty acids, excess salt and unrefined sugar. The rationale for this is the misconception that hypoglycaemia is a product of low food intake, which would seem to suggest their perception of illness and health belief than the understanding of chronic illness. It was concluded that the government and health care professionals have to do more to develop interventions to facilitate good self-management of diabetes among the rural people. Such interventions should address the sufferers’ knowledge of diabetes.